2009
DOI: 10.3390/md7030435
|View full text |Cite
|
Sign up to set email alerts
|

Two New Jaspamide Derivatives from the Marine Sponge Jaspis splendens

Abstract: Two new jaspamide derivatives 2 and 3, together with the parent compound jaspamide (1) have been isolated from the marine sponge Jaspis splendens collected in Kalimantan (Indonesia). The structures of the new compounds were unambiguously elucidated based on 1D and 2D NMR spectral data, mass spectrometry and comparison with jaspamide (1). The new derivatives inhibited the growth of mouse lymphoma (L5178Y) cell line in vitro with IC50 values of <0.1 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
1
38
0
1
Order By: Relevance
“…(2) While oxidation of the Trp is ruinous to nM activity8,10 this does not apply to the β-Tyr residue as activity is retained in 13 in spite of further aryl hydroxylation. (3) Removal or addition of halogens to the Trp is also tolerated as shown by the data of 7 and 8 in comparison to that of 1 9,40. (4) A conformation change in the macrolide ring induced by the Δ2,3 double bond ( 13 vs. 14 ) obliterates nM activity.…”
Section: Resultsmentioning
confidence: 98%
“…(2) While oxidation of the Trp is ruinous to nM activity8,10 this does not apply to the β-Tyr residue as activity is retained in 13 in spite of further aryl hydroxylation. (3) Removal or addition of halogens to the Trp is also tolerated as shown by the data of 7 and 8 in comparison to that of 1 9,40. (4) A conformation change in the macrolide ring induced by the Δ2,3 double bond ( 13 vs. 14 ) obliterates nM activity.…”
Section: Resultsmentioning
confidence: 98%
“…The complete structure of JDC3 was elucidated based on 1 H and 13 C‐NMR, total correlation spectroscopy (TOCSY), heteronuclear multiple‐quantum correlation spectroscopy (HMQC) and heteronuclear multiple‐bond correlation (HMBC) spectral data and were found to be Jaspamide. Jaspamide is a 19‐membered ring made up of four moieties, namely an alanine moiety, an abrine ( N ‐methyl tryptophan) moiety, a β‐tyrosine moiety and a polypropionate moiety (11‐carbon hydroxyl acid containing four methyl groups on alternating carbons) [5,7,26,27]. The presence of each of the four moieties in JDC3 was confirmed by 1D and 2D NMR as follows: (1) The alanine moiety showed 1 H‐NMR signals at δ H 4.71 (quin, 6.7) for H‐15, 0.75 δ H (d, 6.7) for Me‐16 and δ H 6.59 (1H, d , 6.7 Hz) for the N H ‐Ala.…”
Section: Resultsmentioning
confidence: 97%
“…This bioactive substance can exert a pronounced antitumour effect in breast and prostate cancer patients by inducing polymerization of the actin filaments of tumour cells. Recently, two new jaspamide derivatives have been isolated from the marine sponge Jaspis splendens . In vitro experimental results demonstrated that these compounds could effectively suppress rat lymphoma cell L5178Y.…”
Section: Drugs Containing Antitumour Bioactive Peptides With Differenmentioning
confidence: 99%